Dampak Penggunaan Gadget Berlebihan terhadap Perkembangan Kognitif Anak Usia Dini - Lativa, Tania Sonya (Lembaga Yasin AlSys, 2026)
The rapid development of digital technology has increased gadget use among young children and raised concerns about its impact on cognitive development during a crucial phase of brain growth that requires appropriate stimulation to support thinking, memory, and problem-solving abilities. This paper aims to analyze the impact of excessive gadget use on the cognitive development of early childhood, identify factors that trigger high gadget use, and describe preventive efforts that can be undertaken. The method used was a literature study by reviewing various books, scholarly articles, research findings, and policy documents relevant to gadget use and early childhood development. The findings show that excessive and unsupervised gadget use can reduce children’s concentration, memory capacity, language development, and critical thinking skills; conversely, controlled gadget use with educational content and accompanied by parental guidance has the potential to provide benefits as a means of cognitive stimulation. The main factors driving excessive gadget use include uncontrolled duration of use, age-inappropriate content, and lack of parental supervision. The implications of this study underscore the importance of the role of parents and educators in regulating patterns and duration of gadget use so that the cognitive development of young children proceeds optimally, in a balanced manner, and in line with educational goals.